A Christian approach to the Maranao Muslims. - Gomez, Jr., Hilario Molijon, 1941 (South East Asia Graduate School of Theology, 1969)
This thesis considers the ethical aspects of the "Moro problem" in the Philippines as it discusses a Christian approach to the Maranao Muslims of Lanao. The Moro problem, thus, is limited to Muslim-Christian relations in Lanao.
In partial fulfillment of the requirements for the degree of Master of Theology
Thesis (M. Theo.)- South East Asia Graduate School of Theology
Keywords: Moslem problems -- Moral and religious aspects -- Philippines; Christian ethics -- United Church of Christ authors